Sex- and gender-related prevalence, cardiovascular risk and therapeutic approach in metabolic syndrome: A review of the literature. (June 2017) - Pucci, Giacomo; Alcidi, Riccardo; Tap, Lisanne; Battista, Francesca; Mattace-Raso, Francesco; Schillaci, Giuseppe
Graphical abstract: Abstract: Metabolic syndrome (MS), a cluster of metabolic abnormalities linked to insulin-resistance and abdominal obesity, is associated with an increased risk of Type II diabetes mellitus (DM) and cardiovascular (CV) disease. Its prevalence is high, affecting 20%–30% of the general population, and increases with age in a sex-specific manner: in fact, while below 50 years it is slightly higher in men, it reverses after 50 years. The pronounced age-related increase in the prevalence of MS in women occurs as the result of several factors, which may be classified into sex- and gender-related factors. Sex-related factors, linked to genetical and biological pathways, are mainly driven by hyperandrogenism, insulin-resistance, and the associated increase in abdominal obesity and HDL-cholesterol reduction occurring after menopause. Gender-related factors are sensitive to social and cultural behaviors, dietary habits and psychosocial factors. Women are more prone than men to develop MS in response to work stress and low socio-economic status. Sex and gender differences in the prevalence of MS may translate in different CV risk associated. Prospective studies suggest that the CV risk in women with MS is not only equal but also superior to the CV risk of men with MS. This difference is mostly attenuated when adjusting for the presence of overt DM. Despite similar odds for CV events, the number of CV events may be higher in elderly women because of the higher prevalence of MS compared to men in this age group. Men and women may also have a differential response to treatments for MS, such as lifestyle measures and weight loss. Recent observations suggest that men are better responders than women to non-pharmaceutical therapeutic strategies aimed at reducing the prevalence of MS, although this should be confirmed in large-scale studies. The present review describes the impact of sex and gender on the prevalence, clinical presentation, prognostic significance and treatment of the MS. Attention to gender specificities should be a mandatory pre-requisite of clinical and epidemiological research on MS and CV disease, for a better knowledge and development of health strategies.